Systematic Review: Blood Pressure Value Difference Between Measurement with Oscillometric and Auscultation of Patients in Health Services - Dikalita Utami Putri (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Blood pressure is a vital sign that is very important and is a basic physiological parameter in conducting physical assessments of critical patients. Blood pressure can be measured using manual or automatic instruments. The gold standard measures blood pressure with a mercury sphygmomanometer, but its use has been withdrawn due to the risk of mercury contamination. In practice, different values ​​are often obtained between the oscillometric method and auscultation. The objective of this review is to evaluate the significant difference in blood pressure between using the oscillometric method and auscultation in patients in health care. Method A systematic review approach is carried out on research results published in 3 search engines, namely EBSCO, Proquest, and Science Direct. Articles found according to the inclusion criteria that have been set are then assessed using the level of evidence using the NICE approach. The appraisal study uses the Critical Appraisal Skills Program (CASP), and the synthesis method uses a modified PICO. The result indicates that a total of 3 (three) studies were obtained according to the inclusion criteria. The intervention carried out was measuring blood pressure using two methods, namely oscillometric and auscultation. To sum up, there was a statistically significant difference in systolic pressure between the oscillometric and auscultatory methods.